In situ rumen degradation of kernels from short-season corn silage hybrids as affected by processing - Miorin, Renan L. [UNESP]; Holtshausen, Lucia; Baron, Vern; Beauchemin, Karen A. (Oxford University Press (OUP), 2018)
The objective of this in situ study was to evaluate the rumen degradability of kernels from short-season corn hybrids grown for silage in Western Canada (Lacombe, AB) and determine whether decreasing kernel particle size would enhance ruminal degradability in a similar manner for all hybrids. The study was a completely randomized design with 3 beef cows (replicates) and a 6 (hybrid) × 3 (particle size) factorial arrangement of treatments. Kernels were processed to generate three different particle sizes: large (2.3 mm), medium (1.4 mm), and small (0.7 mm). Processed samples were incubated in the rumen for 0, 3, 6, 12, 24, and 48 h using the in situ method and degradation kinetics of DM and starch were determined. Effective rumen degradability (ED) was estimated using a passage rate of 0.04 (ED4), 0.06 (ED6), and 0.08/h (ED8). Hybrids exhibited a range in whole plant DM content (23.7 to 25.0%), starch content (15.9 to 28.1% DM), kernel hardness (21.9 to 34.4 s/20 g) and density (3.57 to 4.18 g/mL), and prolamin content (8.24 to 11.34 g/100 g starch). Differences in digestion kinetics among hybrids were generally more pronounced for starch than DM. The hybrids differed in starch degradability (P < 0.05), with earlier maturing hybrids having lower A fraction, lower kd, and lower ED, with hybrid effects on ED being accentuated with faster passage rate. Kernel DM content (r = -0.85, -0.87), hardness (r = -0.89, -0.86), and density (r = -0.84, -0.85) were negatively correlated with ED4 and ED8 of starch, respectively, due mainly to decreased kd of fraction B. Reducing the particle size of kernels increased ED of starch due to increased A fraction and kd of the B fraction. A tendency (P = 0.09) for hybrid × processing effects for ED6 and ED8 indicated that processing had greater effects on increasing ED of starch for earlier maturing hybrids. We conclude that short-season hybrids that mature early may have lower ED of DM and starch and would benefit from prolonged ensilage time. Kernel processing during silage making is recommended for short-season corn hybrids as a means of enhancing rumen availability of starch.
Keywords: Corn heat unit; Corn silage; Degradability; Grain processing; Starch